MEDIA VISUAL UNTUK MENINGKATKAN MOTIVASI BELAJAR ANAK - Putu Agus Semara Putra Giri (Widyadari : Jurnal Pendidikan, 2021)
This study aims to determine the increase in early childhood learning motivation at Kindergarten Pandu Kumara, Tanjung Bungkak Kelod Denpasar through visual media. And the results of the research show that there is a significant increase. After improving learning using visual media in the first cycle, there is an increase in children's learning motivation with a moving percentage of between 50% and 58%. The range is in the low to quite high category. In the first cycle, there was an increase in the score, but it is still in the original category. Thus it is considered that improvements still need to be done so that the changes achieved by children increase significantly. After looking at several weaknesses in the implementation of learning in cycle I action and improvements in cycle II learning, there is a change in children's learning motivation. Of the 6 children who were made cases, all had increased to a certain extent and had only just reached the high enough category, with a percentage ranging from 58-66%. Overall, it can be stated that the improvement of learning to increase the learning motivation of Pandu Kumara Kindergarten children, using visual media has been successful. So that the action is stopped until cycle II.